Mouse tracker analysis on cognitive awareness - Rosli, D’oria Islamiah (2013)
Lack of human cognitive criteria embedded in system interface design may contribute to the failure of human performance in using system technology. Further, misinterpretation of the availability of resources from the system may also cause accidents to occur at the workplace. Thus, in order to support human cognition, this paper describes cognitive awareness usability testing on system interface design using a mouse tracker analysis. In the study, participants were asked to complete the task scenarios according to cognitive awareness criteria namely perception, comprehension, and projection. Consequently, participants' mouse activity on system powder chemical handling simulation was recorded and analysed using motion tracker software. Most of the participants taking part in this study had experience in working in the industrial sector and more than three years of experience in handling system maintenance. The findings obtained from this study are crucial for other researchers in order to highlight cognitive awareness criteria for system interface design. It is hoped that the findings will help other researchers to better enhance the system design and at the same time to help system users to use the system effectively.